Design of smart wireless street lighting system - Muhamad Fadzil, Che Ani (2017)
The large quantity of electricity of many coountries is consumed in lighting the streets especially in highway. Most of the basic street lighting systems are switched ON/OFF at regular intervals of time. In this thesis, the system is to develop a street light energy saving control system to reduce energy if no vehicles pass through certain roads. Logically, this system may save a large amount of electrical power in a long term. Besides that, this project also may increase the lifetime of the street light lamp as well as reduce the pollutions. The operation of this system is to OFF the street light if no vehicles passing through the road. When the PIR sensor detects movements of the vehicle, the relay that act as a switch will turn ON the street light. Four microcontroller which are Arduino Uno have been used as the controller for the project. In addtition, there are other components used for this system which are PIR sensor, 1 channel 5V relay module and RF 433MHz Transmitter - Receiver module. PIR sensor function as a vehicle detector. The RF 433MHz Transmitter – Receiver module that are inside the circuit will send send and receive information that get from the PIR sensor. Range of the signal from the 433 MHz Transmitter – Receiver module are the key factor that need to be considered to make this system working as desired.